2015
DOI: 10.5194/bg-12-4085-2015
|View full text |Cite
|
Sign up to set email alerts
|

Detection and attribution of global change effects on river nutrient dynamics in a large Mediterranean basin

Abstract: Attributing changes in river water quality to specific factors is challenging because multiple factors act at different temporal and spatial scales, and it often requires examining long-term series of continuous data. Data consistency is sometimes hindered by the lack of observations of relevant water quality variables and the low and uneven sampling frequency that characterizes many water quality monitoring schemes. Nitrate and dissolved phosphate concentration time series from 50 sampling stations across a … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 54 publications
(63 reference statements)
1
5
0
Order By: Relevance
“…Similar shifts in long-term trends regarding nutrient concentrations have been reported in European rivers (Vigiak et al, 2023). For example, we observed that PO 4 -3 concentration shows a slight decreasing trend, possibly related to the wastewater treatments focused on PO 4 -3 reduction (Aguilera et al, 2015). Moreover, NO 3 and NH 4 + showed increasing trends, likely because of the increase in the use of N fertilizers and the expanded number of irrigated lands, crop productivity, and livestock production (Einarsson et al, 2021;Lassaletta et al, 2021).…”
Section: Changes In the Hydrological Regime And Chemistry Trendssupporting
confidence: 82%
See 1 more Smart Citation
“…Similar shifts in long-term trends regarding nutrient concentrations have been reported in European rivers (Vigiak et al, 2023). For example, we observed that PO 4 -3 concentration shows a slight decreasing trend, possibly related to the wastewater treatments focused on PO 4 -3 reduction (Aguilera et al, 2015). Moreover, NO 3 and NH 4 + showed increasing trends, likely because of the increase in the use of N fertilizers and the expanded number of irrigated lands, crop productivity, and livestock production (Einarsson et al, 2021;Lassaletta et al, 2021).…”
Section: Changes In the Hydrological Regime And Chemistry Trendssupporting
confidence: 82%
“…Finally, the low phosphate concentrations observed in the alluvial aquifer, typically below 0.04 mg/l (Menció & Boix 2018), are one-tenth of the values found in surface waters. Such a significant difference suggest that phosphorus inputs mainly originate from other local sources (i.e., industrial activity and WWTP) and could be associated with flood events and sediment transport (Aguilera et al, 2015).…”
Section: Changes In the Hydrological Regime And Chemistry Trendsmentioning
confidence: 99%
“…, asynchronous fluctuations appear to be the rule in disturbed ecosystems, likely associated with dilution of point sources during high flows and enhanced release of reactive phosphorus during warm periods (Aguilera et al, 2015;Bowes et al, 2009;Duan et al, 2012;Minaudo et al, 2015). DSi seasonality also appears to be consistently asynchronous with discharge, due to dilution and seasonal differences in uptake by diatoms (Bowes et al, 2009;House et al, 2001;Moatar et al, 2017;Neal et al, 2000).…”
Section: -mentioning
confidence: 94%
“…The Ebro river delta, the most important delta in the Iberian peninsula, has a mean surface elevation of 0.87 m over the average sea water level, which makes it very sensitive to potential sea level rise, critically threatening nutrient removal dynamics (Genua-Olmedo et al, 2016). Both climate change and agricultural practices have significant impacts on nitrate concentrations in the Ebro basin, while phosphate concentrations are mainly driven by agricultural and industrial practices (Aguilera et al, 2015). In the case of the Jucar River Basin District (Southeast of Spain), temperatures are expected to increase up to 4.86°C in summer by 2040 (Chirivella et al, 2016) and consequently alter nitrogen transformation processes (Temino-Boes et al, 2019).…”
Section: Introductionmentioning
confidence: 99%